An ELISA-based method to quantify osteocalcin carboxylation in mice - Ferron, Mathieu; Wei, Jianwen; Yoshizawa, Tatsuya; Ducy, Patricia; Karsenty, Gerard (Biochemical and biophysical research communications, 2010)
Osteocalcin was recently identified as an osteoblast-secreted hormone regulating insulin secretion and sensitivity. In mice and humans, osteocalcin can be present in the serum in carboxylated or undercarboxylated forms and it has been shown that it is the undercarboxylated form of osteocalcin which acts as a hormone. The study of osteocalcin different circulating forms in mouse serum, however, has been hampered by the absence of quantitative methodology. Here we described a triple enzyme-linked immunosorbent assay (ELISA) system for quantification of mouse total, carboxylated and uncarboxylated osteocalcin. That carboxylation of osteocalcin was decreased in mouse osteoblasts cultures treated with warfarin, an inhibitor of carboxylation validated this assay. This ELISA could also detect elevated levels of undercarboxylated osteocalcin in the serum of mice treated with warfarin and in the serum of Esp −/− mice, a mouse model known to have more undercarboxylated, i.e., active osteocalcin. These results show that this new ELISA system is a reliable method to assess carboxylation status of osteocalcin in cell culture supernatants as well as in mouse serum. Its use should facilitate the analysis of culture system or mouse model in which the hormonal activity of osteocalcin needs to be evaluated.